Edukasi Pengelolaan Limbah Plastik bagi Masyarakat Pesisir melalui Penyuluhan di Posyandu dan Sekolah di Kelurahan Nunukan Timur - Ana Welellu; Zamli Zamli; Sudirman Sudirman (BADAN PENERBIT STIEPARI PRESS, 2025)
Coastal areas often face serious challenges related to environmental pollution, one of which comes from poorly managed plastic bottles used as seaweed floats. This waste not only pollutes the waters but also negatively impacts the marine ecosystem and the health of the surrounding community. This community service activity aims to increase knowledge and awareness of coastal communities, particularly housewives and elementary school students, regarding the impacts of plastic waste and the importance of environmentally friendly waste management. The outreach program was conducted over six days in Nunukan Timur Village, Nunukan Regency, targeting three integrated health posts (Posyandu) and three elementary schools. The methods used included interactive lectures, group discussions, waste sorting simulations, and the use of visual media such as posters and educational videos. The results of the activity demonstrated high participant enthusiasm, as evidenced by active participation during the outreach and discussion sessions. However, it was also found that most residents were aware of the dangers of littering but did not yet have adequate alternatives for managing plastic waste. Limited waste management facilities were a major obstacle. Nevertheless, this activity succeeded in building participant motivation to care more about the surrounding environment and begin implementing simple practices such as sorting household waste and reducing the use of single-use plastics. Thus, community-based education has proven to be an effective strategy for building environmental awareness and encouraging behavioral change. However, the sustainability of such programs requires the provision of infrastructure and local government policies that support sustainable environmental management.